1974
DOI: 10.9753/icce.v14.44
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Threshold Under Oscillatory Waves

Abstract: As the velocity of the water motion near the bottom under oscillatory waves is increased, there comes a stage when the water exerts a stress on the particles sufficient to cause them to move. This study reviews data on threshold of sediment motion under wave action and compares the results with the established curves for threshold under a unidirectional current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 8 publications
(7 reference statements)
6
29
0
1
Order By: Relevance
“…() findings. However, the boundary separating rolling from saltation transport modes varies within the 7 to 9 m s –1 interval for the largest particles which clearly exceeds the range predicted by Nott () but roughly agree with results derived from Komar and Miller ().…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…() findings. However, the boundary separating rolling from saltation transport modes varies within the 7 to 9 m s –1 interval for the largest particles which clearly exceeds the range predicted by Nott () but roughly agree with results derived from Komar and Miller ().…”
Section: Resultssupporting
confidence: 89%
“…Komar and Miller (), Hallermeier () and Soulsby () addressed the issue of threshold wave height required to induce motion of particles resting in the sea floor and compared computed results with experimental data. Application of Airy wave theory in combination with the latter solutions makes it possible to convert flow velocities necessary to induce motion to maximum orbital velocities near the bottom of the sea associated with near‐breaking wind waves.…”
Section: Discussionmentioning
confidence: 99%
“…Komar & Miller (1974) found that the diagram is approximately valid also for turbulent rough oscillatory flow down to a grain size of 0 .1 mm . For particles of 0 .1 mm the shear velocity is about 1 cm s -'.…”
Section: Critical Shear Stressmentioning
confidence: 84%
“…For non-cohesive material and uni-directed flow, the critical shear is determined from the Shields diagram . Komar & Miller (1974) found the diagram to be valid for oscillatory flow when the grain size exceeded 0 . divided by density of water) .…”
Section: Erosion Theorymentioning
confidence: 99%